Impact of meteorological disaster shocks and collective action on farmers' adoption of soil and water conservation technologies: evidence from the Loess Plateau, China - Ding, Xiuling; Li, Lipeng; Lu, Qian; Zhang, Weiping (Frontiers in Sustainable Food Systems, 2025)
IntroductionHighlighting the importance of addressing the meteorological disaster shocks (MDS) experiences of potential adopters, alleviating disaster-induced anxiety, and harnessing risk aversion psychology, along with promoting the essence of collective action, can be crucial in facilitating the adoption of soil and water conservation technologies (SWCT).MethodsThis study delves into the intricate dynamics governing the adoption of SWCT among grain growers. This study draws on field survey data from 1,106 farming households across three provinces. Using a binary Probit model and mediation effect analysis, it explores how MDS and collective action influence farmers' adoption of SWCT.ResultsThe results reveal several key findings. First, MDS significantly and positively affect farmers' adoption of different types of SWCT. Second, collective action also has a significant positive impact on SWCT adoption. Third, collective action mediates the relationship between MDS and SWCT adoption, indicating that part of MDS's influence is transmitted through collective action. Finally, heterogeneity analysis shows that the impact of MDS on SWCT adoption varies significantly across farmer subgroups defined by age, education level, and planting scale. Likewise, government subsidies, total household land management area, and the number of household agricultural machinery significantly affect farmers' decisions to adopt SWCT.Discussion and suggestionsBased on the research, the following suggestions are put forward: promote adaptive technologies and strengthen demonstrations and guidance; improve meteorological early warning, establish a disaster case database, and subsidize disaster-stricken farmers; support cooperatives in participating in technology promotion and reward excellent organizations; for farmers aged 55 and below with low educational levels, promote simple technologies, strengthen training, increase subsidies, and drive adoption through demonstrations; optimize subsidy policies, allocate technologies based on resources, and establish an evaluation mechanism for dynamic policy adjustment.